Leitliniengerechte stationäre psychiatrisch-psychotherapeutische Behandlung der Borderline-Persönlichkeitsstörung: Normative Personalbedarfsermittlung = Guideline-adherent inpatient psychiatric psychotherapeutic treatment of borderline personality disorder - Bohus, Martin; Schmahl, Christian (Der Nervenarzt, 2016)
Background: Borderline personality disorders (BPD) are severe mental diseases which place high pressure on the psychiatric healthcare system. Nowadays, well-tested, disorder-specific treatment concepts are available also for inpatient treatment in Germany. These show very good and long-term improvements in the psychopathology as well as posttreatment social participation; however, prerequisites for the implementation of these evidence-based inpatient psychotherapy programs are well-trained treatment teams and appropriate financing of resource expenditure. Objective: The aim was to formulate a definition of normative needs for treatment duration and intensity for a guideline-conform, empirically proven and effective inpatient treatment of borderline personality disorder as well as the derived personnel requirements in comparison to the currently available resources within the framework of the Psychiatry Personnel Act (Psych-PV). Material and methods: The resource requirements were established based on evaluated hospital ward models, the recommendations of the S2 guidelines and the criteria of specialist societies and compared with the personnel stipulations according to the Psych-PV. Results: The results for a normatively established treatment program showed a pronounced deficit in the financing of the evaluated resource requirements, even when the stipulations laid down in the Psych-PV were implemented to 100 %. Discussion: Disorder-specific inpatient treatment programs for borderline personality disorder have been scientifically proven to be highly effective; however, resource analyses show that the personnel requirements necessary for effective implementation of these programs are much higher than those allocated by the funding according to the Pysch-PV. The current underfunding leads to inadequate treatment outcomes with high readmission rates and as a result high direct and indirect costs of illness.